Characteristics of people committing suicide in Medellín, Colombia (2005)
ABSTRACT: Objectives Describing the socio-demographic and clinical chara teristics of a group of individuals who committed suicide in the city of Medellin between 2000 and 2003; identifying possible groups within the suicides’ socio-demographic and clinical characteristics. Methods The sample consisted of 108 individuals who had committed suicide in Medellin; psychological autopsy was carried out and their characteristics were described. Multiple correspondence analysis was used for identifying the different groups. Results 50 % of the individuals were aged less than 29 and 79,4 % were male. The most frequently employed method for committing suicide was hanging (47,2 %); 68,5 % had expressed a wish to die and 35,2 % had previously attempted suicide. Three axes were identified for expressing the socio-demographic and clinical characteristics. Conclusions The characteristics found in this study were similar to those reported in studies carried out in Colombia and other countries. Suicide was more frequent amongst younger people in the group being studied, this being consistent with the national tendency. The groups observed in multiple correspondence analysis were in line with clinical observations and can be used for designing prevention strategies. However, further analytical studies are required for determining the actual risk factors and using them as the starting point for a prevention programme.